(untitled) (Annals of Library and Information Studies, 2024)
In the field of extension education, scientometric analysis has been conducted in Web of Science Databases over a period of ten years, and the objective of this study is to explore the significance of this analysis. Researchers in the field of extension education may find the information that this study gives on the trends in research and what is currently taking place in the field of extension education to be beneficial because it provides information about the patterns that appear in research. The topic of this study is to emphasize the literature that has been contributed by various nations on a worldwide scale, the literature that has been contributed by affiliations, the top ten most referenced literature in the field of extension education, and the keywords that have been used frequently by the writers. In order to accomplish the goals of this study, a total of 32399 articles were gathered from the databases. Extending education was the keyword used for filtering the document, and only articles were selected for inclusion in the collection which were taken from the years 2014-2023. The software known as biblioshiny is utilized to carry out the data analysis for this paper.